Pengaruh Viral Marketing, Online Customer Review, Impulse Buying terhadap Keputusan Pembelian Produk Glad2Glow di TikTok Shop pada Remaja di Surabaya - Nathania Ariyani Paramesti Anindya; Ayun Maduwinarti; Ni Made Ida Pratiwi (Global Leadership Organizational Research in Management, 2025)
In today’s digital era, social media platforms like TikTok are not only used for entertainment but have also become popular shopping platforms, especially among teenagers. One product that has gained significant attention is Glad2Glow, which utilizes TikTok Shop to market its products. The marketing strategies employed include viral marketing, online customer reviews, and the stimulation of spontaneous purchases (impulse buying).This study aims to determine whether these three variables have a significant influence on the purchasing decisions of teenagers in Surabaya regarding Glad2Glow products on TikTok Shop. A quantitative approach was used, with questionnaires distributed to teenagers in Surabaya as respondents. The data analysis technique applied was multiple linear regression to test the influence of each independent variable on purchasing decisions as the dependent variable. The results show that viral marketing, online customer reviews, and impulse buying all have a significant impact on purchasing decisions. This indicates that digital marketing strategies that are engaging, informative, and capable of triggering spontaneous purchases can enhance teenagers’ purchasing decisions on platforms like TikTok Shop.